Exploring School Teachers' Cyber Security Awareness, Experiences, and Practices in the Digital Age - R Ravichandran; Sonam Singh; P Sasikala (Journal of Cybersecurity Education, Research & Practice)
This study investigates the awareness and practices of cyber security among school teachers, exploring their understanding of cyber threats, online behaviours, and response mechanisms to cyber incidents. A structured questionnaire was administered to gather data on demographic information, cyber security training, online practices, and experiences with cybercrime. The findings reveal varying levels of awareness among teachers, with many reporting limited knowledge of prevalent cyber threats such as phishing and identity theft. Despite the increasing reliance on digital tools for teaching, a significant number of respondents indicated a lack of formal training in cyber security. The study highlights the necessity for targeted awareness programs and training initiatives to enhance teachers' understanding of cyber safety measures and reporting mechanisms. Furthermore, the research underscores the importance of fostering a culture of cyber security in educational institutions to better protect both educators and students from potential online threats.